Association between lifestyle behaviors and health-related quality of life among primary health care physicians in China: A cross-sectional study - Lin, Yisha; Huang, Yuankai; Xi, Xiaoyu (Frontiers in Public Health, 2023)
Background: Primary health care (PHC) physicians take on significant obligations to provide health care services in the pursuit of Universal Health Coverage (UHC). PHC physicians' health-related quality of life (HRQoL) can have a strong impact on patients, physicians and the health care system. Lifestyle interventions are found to be effective to improve HRQoL. The purpose of this study was to evaluate the association between lifestyle behaviors and HRQoL among PHC physicians, so that lifestyle intervention can be tailored by policy makers for health promotion. Methods: A cross-sectional survey was conducted in China and data on sociodemographic, lifestyle behaviors and HRQoL was collected by a self-administered questionnaire. HRQoL was measured through EuroQol-five dimension-five level (EQ-5D-5L) instrument. A Tobit regression model was performed to evaluate the association between sociodemographic characteristics, lifestyle behaviors and HRQoL. Results: Among 894 PHC physicians who completed the survey, Anxiety/Depression (AD) is the dimension with the most problems reported (18.1%). Regular daily routine (β = 0.025, 95%CI 0.004 to 0.045) and good sleep quality (β = 0.049, 95% CI = 0.029 to 0.069) were protective factors for HRQoL, while smoking (β = -0.027, 95% CI = -0.079 to -0.003) and frequency of eating breakfast (β = -0.041, 95%CI = -0.079 to -0.003) were associated with poorer HRQoL. Physical activity and alcohol drinking were not significantly associated with HRQoL. Conclusion: These findings suggest that tailored interventions on daily routine, improving sleep quality, and tobacco control among PHC physicians may be effective strategies to improve HRQoL.